The Limits of Tolerance: Extreme Speakers on Campus. (18th June 2020) - Boch, Anna
Abstract: Recently, colleges and universities across the United States have had to choose whether to allow controversial speakers on campus. This study uses a factorial experiment to investigate individual features of controversial speaker events, including student opinion, security risk, and actual event-based descriptions of extreme left and extreme right speakers. Contrary to earlier studies of political tolerance, this study finds that Republicans (and ideological conservatives) are slightly more tolerant of extreme speech than are Democrats and liberals. However, this difference is attenuated by three factors. The first is order effects: if Democrats are first asked about an extreme left speaker, they are then more tolerant of an extreme right speaker. Second, concerns about the possibility of harm resulting from the speech partially explain Democrats' intolerance of the extreme right speaker. Third, asymmetric polarization has resulted in extreme right ideas entering the mainstream more than ideas from the far left; thus Democrats face a more arduous test of the classic liberal commitment to tolerance. Finally, this study contributes to the political tolerance literature by testing tolerance of new, extreme speaker targets on both the ideological left and right than what has previously been studied.